2018
DOI: 10.1107/s2056989018008277
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of diethyl {2,2,2-trichloro-1-[2-(1,3-dioxo-2,3-dihydro-1H-isoindol-2-yl)-4-methylpentanamido]ethyl}phosphonate

Abstract: The crystal structure of the inter­mediate product of the synthesis of phospho­rylated 5-amino-1,3-oxazol-4-yl­phospho­nic acid derivatives is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…For selected interatomic bond distances in the optimised molecular structures, P=O range from 1.4560 Å to 1.4646 Å, and C=O range from 1.2065 Å to 1.2141 Å (NA to ND), except for NE in which C=O bond is relatively longer (1.4615 Å) due to its separation from P=O group by a methylene group. All the bond distances are within the usual ranges reported in the literature for the same bonds in similar compounds, either as isolated ligands or complexes (Conary et al, 1991;Conary et al, 1993;Breuer, 1996;Brovarets et al, 2018 The effects of both sulphonyl and -CH groups as 2 may apply to each compound could also be seen on the bond lengths of amide the C=O, which decrease with increasing electron-withdrawing effect. The C-O bonds of the alkoxy groups generally exhibit different bond lengths due to their appearance in different chemical environments, as already observed in the NMR data.…”
Section: Molecular and Electronic Structures From Dft Calculationssupporting
confidence: 72%
“…For selected interatomic bond distances in the optimised molecular structures, P=O range from 1.4560 Å to 1.4646 Å, and C=O range from 1.2065 Å to 1.2141 Å (NA to ND), except for NE in which C=O bond is relatively longer (1.4615 Å) due to its separation from P=O group by a methylene group. All the bond distances are within the usual ranges reported in the literature for the same bonds in similar compounds, either as isolated ligands or complexes (Conary et al, 1991;Conary et al, 1993;Breuer, 1996;Brovarets et al, 2018 The effects of both sulphonyl and -CH groups as 2 may apply to each compound could also be seen on the bond lengths of amide the C=O, which decrease with increasing electron-withdrawing effect. The C-O bonds of the alkoxy groups generally exhibit different bond lengths due to their appearance in different chemical environments, as already observed in the NMR data.…”
Section: Molecular and Electronic Structures From Dft Calculationssupporting
confidence: 72%
“…More recently, a urea compound with two phthalimides showedstacking and intramolecular hydrogen bonding (PONZEZ; Medrano et al, 2014). Three structures with only one phthalimide group have also showninteractions (VIDTUA; Brovarets et al, 2018;PAVHUR;Yang et al, 2012;SAGTIF;Shao et al, 2012). Another compound has been reported that has two phthalimide-protected nitrogens with two carbon spacers versus three for the title compound, a benzyl group, and a trityl sulfide (WOJSIZ;Flö rke et al, 2014).…”
Section: Database Surveymentioning
confidence: 99%